Efficient radiative cooling based on spectral regulation and atmospheric water harvesting with sunflower design - Tao Ma; Jiangbo Wu; Xiaoze Du; Shujun Liu (iScience)
Summary: Inspired by the fog-collecting abilities of the Namib Desert beetle, researchers have developed wettability-engineered surfaces for fog collection. However, these approaches fall short in arid regions where fog is absent. To address these challenges, we developed a dual-sided structure based on radiative cooling. The radiation cooling material on the upper surface can achieve energy free cooling. The lower surface is a pattern with heterogeneous wettability, composed of wedge-shaped and conical structures, which can achieve rapid droplet accumulation and directional transport. The radiation cooling material adjusted by spectrum can achieve a temperature difference of up to 14.2°C, enabling the composite material to achieve a maximum water collection efficiency of 602.5 g·m-2·h-1 under RH of 80% conditions. This study provides an effective solution to alleviate water scarcity in arid regions.